The local chief executives: a comparative study of international experiences focusing on the role of governors in Egypt - Mahmoud, Nahla Mahmoud (AUC Knowledge Fountain, 2012)
The 25th January Revolution has inspired the Egyptian citizens for achieving change as one of the main Revolutionary goals. In the spirit of the revolution, reforming the local administration system and the role of governors as a part of it will achieve the local developmental goals. This research aims investigate the responsibilities,competencies and relationships of the local chief executives as found in international experiences. It will then try to choose some cases according to certain criteria and discuss the current status of governors in Egypt in order to suggest the lessons learned for Egypt after the Revolution. In order to examine the research question, the current study used qualitative research design by interviewing local administration's experts. This methodology will allow the researcher to provide the decision makers(member of the peoples' assembly and new president) with various alternatives concerning local administration reform and the new proposed law. Stressing the differences between the local chief executive in the international experiences and the role of governors in Egypt while highlighting the problems they face in the reform process, especially at that time, are fundamental in understanding the inevitability of reform. The seven interviewees developed indispensable recommendations for the decision makers in reforming the role of governors on the short and long run; for example, highlighting decentralization' principals in the new constitution, developing a simple structure of local administration system, electing the governors and empowering them through increasing their responsibilities and real authorities. Moreover, balancing the relationship between the local councils and governors through "no confidence vote", holding governors accountable mainly in front of the local citizens and many other alternativescomprehensively discussed in last chapter of the research. Results indicated that Fiscal and administrative decentralization, local governance principals, responsiveness to the local citizens' needs, and many other issues have been among the main dilemmas highlighted by the experts in reforming the local administration system of Egypt . In addition, various alternatives for reforming the governors' function along with the main competencies, responsibilities and the relationship with the central government and local citizens are explored. Regardless the difference among the experts in tackling these issues, they agreed that there are some crucial criteria in the process of reforming local administration in Egypt